Justification of the renoprotective action of the mixture of sodium chloride and sodium bicarbonate solutions in phenylhydrazine intoxication - V. Sirman; B. Nasibullin; S. Gushcha; N. Badyuk; Yu. Dekhtyar; A. Gozhenko (Kazimierz Wielki University, 2023)
The authors conducted a study on 35 white Wistar outbred rats to investigate the possibility of correcting acute kidney damage induced by the administration of phenylhydrazine at a dose of 100 mg/kg by introducing a mixture of sodium chloride and sodium bicarbonate solutions into the body. The research results identified changes in the kidneys upon phenylhydrazine administration, including the loss of some capillary glomeruli, eosinophilic deposits in Bowman's spaces and tubular lumens, and lymphoid infiltration in the interstitium. Rats receiving a mixture of sodium chloride and sodium bicarbonate solutions in their drinking water showed positive changes in their kidneys: no loss of capillary glomeruli was observed, and eosinophilic deposits were absent in most tubules. Lymphocyte aggregation was only observed around some renal vessels. The authors suggest that the intake of additional sodium and bicarbonate into the body, along with alkalinization of the primary urine, promotes the excretion of hemolysis products caused by phenylhydrazine, which contributes to renoprotection and preservation of renal parenchyma.